2017
DOI: 10.17507/tpls.0707.04
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Knowledge and Metacognitive Control of Writing Strategy between High- and Low-performing Chinese EFL Writers

Abstract: Abstract-This study investigated metacognitive knowledge and control of writing strategy in English among 65 Chinese EFL learners in two argumentative writing tasks. Metacognitive knowledge was measured using a questionnaire written in simple present tense. Metacognitive control required writers to respond to a questionnaire written in simple past tense immediately following completion of each writing task according to the actual strategy use in the writing tasks. Students were grouped into high-and low-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Another possible explanation for the more strategic behaviors by the high-achieving students could be that they had a relatively large strategic repertoire to draw upon (i.e., strategic knowledge) than low-achieving peers. However, as the study did not measure strategic knowledge, which is stable, enduring, and trait like dispositions ( Phakiti, 2003a , b , 2006 , 2008a , b ; Westby, 2004 ; Han and Stevenson, 2008 ; Han, 2012 ; Flavell, 2016 ; Wang and Han, 2017 ), it is hard to verify such speculation. To explicate the complicated relationship between strategic knowledge, strategic processing, and language performance in language tests among young children, future studies may consider measuring both trait-like knowledge of strategies and context-specific strategic processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible explanation for the more strategic behaviors by the high-achieving students could be that they had a relatively large strategic repertoire to draw upon (i.e., strategic knowledge) than low-achieving peers. However, as the study did not measure strategic knowledge, which is stable, enduring, and trait like dispositions ( Phakiti, 2003a , b , 2006 , 2008a , b ; Westby, 2004 ; Han and Stevenson, 2008 ; Han, 2012 ; Flavell, 2016 ; Wang and Han, 2017 ), it is hard to verify such speculation. To explicate the complicated relationship between strategic knowledge, strategic processing, and language performance in language tests among young children, future studies may consider measuring both trait-like knowledge of strategies and context-specific strategic processing.…”
Section: Discussionmentioning
confidence: 99%
“…McNamara (1996) and Phakiti (2008a) postulate that strategic competence encompasses two components: strategic knowledge and strategic processing. While strategic knowledge is considered being relatively stable and stored in the long-term memory ( Han and Stevenson, 2008 ; Phakiti, 2008a , b ; Han, 2012 , 2013 ; Wang and Han, 2017 ); strategic processing is related to the online information processing and heavily hinges upon the contexts, hence relatively unstable ( Schmidt, 2001 ; Cohen, 2007 ). The postulation of the construction of strategic competence has also been validated and the stability of the construct has also been established in Phakiti’s, (2008a , b ) longitudinal studies, which showed a clear distinction between strategic knowledge and strategic processing in a customarily designed FL reading testing context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past researchers make evident the positive influential role of metacognition in academic achievement and learning (Artelt et al, 2010;Dimmit & McCormick, 2012;Dunlosky & Metcalfe, 2009;Efklides, 2014;Gaskill & Hoy, 2002;Hacker, Bol, & Keener, 2008;Thillmann, 2008;Winne & Nesbit, 2010) in various domains, such as mathematics (Callan & Cleary, 2018;De, Desoete, & Roeyers, 2000;Desoete, Roeyers, & Buysse, 2001;Desoete, Roeyers, & De Clercq, 2003), language and physical education (Stephanou & Mpiontini, 2017), reading competence (Soodla, Jõgi, & Kikas, 2016), language learning (Wang & Han, 2017), writing and reading (Chonan & Sawa, 2009;Harris, Santangelo, & Graham, 2010), music (Barbara & Alessandro, 2017), learning and performing better in the classroom (Pintrich, 2002), emotions in learning situations (Efklides, 2011(Efklides, , 2016Karagiannides, Barboukis, Gourgoulis, Kosta, & Antoniou, 2015) and problem solving (Antonietti, Ignazi, & Perego, 2000).…”
Section: Metacognition and Academic Achievementmentioning
confidence: 99%
“…cognitive, affective, social, and metacognitive). L2 writing also involves interactions between internal factors (e.g., first language (L1) writing abilities) and external factors (e.g., guidance of writing tasks, audience) (Hyland, 2003;Wang & Han, 2017). One of the concerns being discussed by educators and researchers is what makes successful students differ from unsuccessful ones.…”
Section: Introductionmentioning
confidence: 99%